Perceived Trustworthiness and Perceived Risk-Taking as Predictors of Online Shopping Behaviour among Youths in Ibadan - Emmanuel E. Uye; Tobi S. Onifade; Esohe G. Ehondor (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
E-commerce has generated a lot of interest across the globe where individuals sit in the comfort of their homes and purchase goods and services. However, study linking youths in many developing countries to the new trend seem to be affected by skepticism. Therefore, this study examines perceived trustworthiness and perceived risk-taking as predictors of online shopping behavior among youths in Ibadan metropolis. Cross-sectional survey design was adopted while data were collected from 200 randomly selected participants. Data were collected using validated scales and analyzed using zero-order correlation, t-test for independent samples, and multiple regression analysis to test three hypotheses at a p < 0.05 level of significance. The result revealed that perceived trustworthiness and perceived risk-taking significantly correlated with online shopping behavior among study participants. Also, the results revealed that perceived trustworthiness and perceived risk-taking jointly predicted online shopping behavior. Finally, both perceived trustworthiness and perceived risk-taking independently predicted online shopping behavior among study participants. The study concluded that perceived trustworthiness and perceived risk-taking are excellent predictors of online shopping behavior among those who took part in the study. It is advised that web designers and internet marketers create online shopping platforms that foster confidence and discourage risk-taking in order to attract and retain more online customers.